A macro‐model for describing the in‐plane seismic response of masonry‐infilled frames with sliding/flexible joints. (10th August 2022) - Dhir, Prateek Kumar; Tubaldi, Enrico; Pantò, Bartolomeo; Caliò, Ivo
Abstract: Masonry infill walls are among the most vulnerable components of reinforced concrete (RC) frame structures. Recently, some techniques for enhancing the performance of the infills have been proposed, aiming at improving both the global and the local behaviour of the infilled frame structure. Among the most promising ones, there are those that aim to decouple or reduce the infill‐frame interaction by means of flexible or sliding joints, relying respectively on rubber or low‐friction materials at the interface between horizontal subpanels or between the panels and the frame. Numerous models have been developed in the last decades for describing the seismic response of masonry‐infilled RC frames, but these have focused mainly on the case of traditional infills. This study aims to fill this gap by proposing a two‐dimensional macro‐element model for describing the in‐plane behaviour of RC infilled frames with flexible or sliding joints. The proposed modelling approach, implemented in OpenSees, is an extension of a discrete macro‐element previously developed for the case of traditional infill panels. It is calibrated and validated in this study against quasi‐static tests from the literature, carried out on masonry‐infilled RC frames with sliding and rubber joints. The study results show the capabilities of the proposed modelling approach to evaluate the benefits of using flexible joints in terms of minimising the negative effects of the interaction between infill and RC frame and limiting the increase of global stiffness of the system with respect to the bare frame condition.